ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMK SETELAH MENGIKUTI PEMBELAJARAN BERBASIS MASALAH - Ario, Marfi (Edu Research, 2016)
Mathematical reasoning ability is one of the important and fundamental skills in mathematics. Mathematical reasoning skills students can improve through a learning that requires involvement of the student in building his own knowledge. One isthrough problem based learning. This research is a descriptive qualitative with the aim to determine the level of mastery of mathematical reasoning abilities of students after participating in problem based learning and determines the range of the mistakes made by students in answering questions of mathematical reasoning abilities. The method used is method of testing, observation, and interviews. The results showed that students' mathematical reasoning skills after participating in problem-based learning is good. Variety mistakes made by students are do not understand of questions, misconceptions, mistakes perform arithmetic operations, and error using the formula.